PENGARUH PEMANASAN BIJI KACANG Pisum sativum L var. "Belinda" DENGAN SINAR INFRA MERAH TERHADAP NILAI DAYA CERNA DAN ENERGI METABOLISME NITROGEN TERKOREKSI PACA AYAM - Patuan L.P. Siagian (Jurnal Kimia Terapan Indonesia, 1998)
Legume seed of peas (Pisum sativum) was radiated by infrared of 2450 MHz for 0, 80 and 100 seconds in a gas-type experimental radiator. Three levels of initial seed moisture content (13%, 17%, and 21%) was regulated by the moistening double-spiral mixer. The apparent digestibility of the nutrients of the treated seeds was evaluated using 96 five-week old male chicks of LSL-Brown in a full automatically adjustable climate conditioned room.The results of this experiment showed a Significant increase of nutrient digestibility of the peas by infra-red treatment; p 0.01 for fat, p 0,001 for dry matter, organic matter, starch, and nitrogenfree extract. The exposure time to infra-red treatment/or lOa seconds (seed temperature 0f 115 °C) increased limiting amino acids digestibility, namely lysine from 84.51% to 91.47%, threonine from 73.24% to 81.37%. and methionine from 61.20% to 77.70%.